The Spanish "Century XXI" academy for developing elite level basketballers: design, monitoring and training methodologies. Issue 2 (2nd April 2016) - Calleja-González, Julio; Mielgo-Ayuso, Juan; Lekue, José Antonio; Leibar, Xabier; Erauzkin, Julen; Jukic, Igor; Ostojic, Sergej M.; Delextrat, Anne; Sampaio, Jaime; Terrados, Nicolás
ABSTRACT: Objectives : The XXI Century Academy was a 6-year state-initiated intervention program that served as an alternative to basketball clubs for players in the u-14 and u-18 age groups in Spain, under guidelines established by the Spanish Basketball Federation. It was an important and unique project on talent development in basketball. To the best of the authors' knowledge, no evidence has been reported on long-term athlete development programs in basketball worldwide. The main aim of this report is to describe the design and evaluation methods used for the XXI Century Academy as a long-term intervention program in the elite Spanish Basketball Academy, aiming to prepare basketball players to compete at the elite level. Methods : The monitoring time lasted from 1996 to 2001. A total of 55 players were assigned to the intervention groups based on age, position, maturation level, and country of origin. During this process, participants competed in up to two categories in addition to playing competitive official matches worldwide in international tournaments in their categories and with the national team in the European and World Championships (u-14 - u-18). Participants included 1 NBA player, 3 national A Team players, 10 ACB (First Spanish League) players, 5 LEB (second League) players and 39 LEB-2 EBA (third League) players. Assessments took place in a High-Performance Sports Center (CPT FADURA-GETXO- Basque Government, Getxo, Vizcaya, Spain) and consisted of health questionnaires, anthropometric measures, blood parameters, maturation level, birth age, fitness tests, training volume and intensity, physical activity, technical and tactical training, dietary intake, supplementation and injuries. Each player was assessed 4 times per year (September, December, April, June) for 4 years (16 data points). Results : This is a purely methodological paper describing the design and evaluation methods used in the XXI Century Project, which will be used as a basis for future reporting of results. Therefore, the results of the project will be reported in subsequent publications. Conclusion : The viability of the Century XXI Project protocols has been described. This national project of training in basketball closely replicates the physical and technical match-play conditions for professionals and may constitute a useful training tool.